How is Artificial Intelligence Changing Consumer Behaviour in Indonesia? Potential and Implications for Society - Hikmah; Nurhidayanti; Onri Bunga; Tedy Kurniawan; Achmad Adriyanto (IECON: International Economics and Business Conference, 2024)
Artificial Intelligence (AI) plays an increasingly important role in the marketing sector in Indonesia, in line with rapid technological developments and digitalization. The aim of this research is (1) to find out how Artificial Intelligence changes consumer behaviour (2) to find out its potential and implications for society. This research uses a qualitative approach with a focus on literature studies, this analysis is to find out how AI changes consumer behaviour and what its potential and implications are for Indonesian society. The research results show that AI creates a more personalized, efficient and safe shopping experience for Indonesian consumers. As for the potential and implications for society, namely: Overall, the potential for AI in Indonesia is very large, but it needs to be balanced with attention to the social, economic and ethical implications that may arise. A thoughtful and collaborative approach between government, industry and society will be key to maximizing the benefits of AI while minimizing its risks